Research on coordinated control method of urban traffic based on neural network. (7th March 2022) - Niu, Lede; Pan, Mei
Due to the complexity of data in urban traffic coordination and control, there is a lack of relevance between data nodes of existing coordination methods, which leads to urban traffic holdup and congestion. A coordinated urban traffic control method based on neural network is proposed. The traffic flow prediction model is constructed to predict and calculate the urban traffic flow, green signal ratio, phase and period. The coordinated control method based on neural network is used to fine-tune the traffic signal, green signal ratio, phase and cycle, so as to improve the traffic capacity at the intersection during the peak period, and finally realise the coordinated control of urban traffic. The simulation results show that the proposed method can effectively alleviate the traffic capacity at intersections, and the time required for the method to run the whole process is less, which indicates that the proposed method is effective and reliable.